Translanguaging as Dynamic Activity Flows in CLIL Classrooms - Lin, Angel M. Y.; He, Peichang (Journal of language, identity, and education, 2017)
In this article, the role of translanguaging in facilitating content and language integrated learning (CLIL) is examined in connection with the notion of academic language across the curriculum in multilingual contexts. Ethnographic naturalistic observations and interviews were conducted to analyse translanguaging in the dynamic flow of interactions among South Asian ethnic minoritized students and their science teacher in a CLIL classroom in Hong Kong. The analysis shows that despite dominant school and government policies that impose a monolingual medium of instruction, translanguaging naturally flows from the dynamic interactions and activities in the classroom as both teacher and students are intensely engaged in meaning making about the lesson topics. Drawing on a recent theoretical explication of translanguaging and flows, the notion of translanguaging is further explicated with new theoretical and empirical import from the distributed language view. Pedagogical implications for CLIL are discussed.